Effect of Environmental pH on Mineralization of Anaerobic Iron-Oxidizing Bacteria - Jiang, Na; Feng, Yiqing; Huang, Qiang; Liu, Xiaoling; Guo, Yuan; Yang, Zhen; Peng, Chao; Li, Shun; Hao, Likai (Frontiers in Microbiology, 2022)
Freshwater lakes are often polluted with various heavy metals in the Anthropocene. The iron-oxidizing microorganisms and its mineralized products can co-precipitate with many heavy metals including Al, Zn, Cu, Cd, and Cr. As such, microbial iron oxidation can exert a profound impact on environmental remediation. The environmental pH is a key determinant regulating microbial growth and mineralization and then influences the structure of the final mineralized products of anaerobic iron-oxidizing bacteria. Freshwater lakes, in general, are neutral-pH environments. Understanding the effects of varying pH on the mineralization of iron-oxidizing bacteria under neutrophilic conditions could aid in finding out the optimal pH values that promote the coprecipitation of heavy metals. Here, two typical neutrophilic Fe(II)-oxidizing bacteria, the nitrate-reducing Acidovorax sp. strain BoFeN1 and the anoxygenic phototrophic Rhodobacter ferrooxidans strain SW2, were selected for studying how their growth and mineralization response to slight changes in circumneutral pH. By employing focused iron beam/scanning electron microscopy (FIB-SEM) and transmission electron microscopy (TEM), we examined the interplay between pH changes and anaerobic iron-oxidizing bacteria and observed that pH can significantly impact on the microbial mineralization process and vice versa. Further, pH dependent changes in the structure of mineralized products of bacterial iron oxidation were observed. Our study could provide mechanical insights into how to manipulate microbial iron oxidation for facilitating remediation of heavy metals in the environment.